UJI TOKSISITAS DAN IDENTIFIKASI EKSTRAK ETANOL SPONS Callyspongia aerizusa TERHADAP LARVA Artemia salina L. - Rahayu, Made Rai; Sibarani, James; Swantara, I Made Dira (CAKRA KIMIA (Indonesian E-Journal of Applied Chemistry); Volume 1, No. 1, 2013, 2013)
Identification of active compounds extracted from marine sponge C allyspongia aerizusa and their toxicity against  Artemia salina L. larvae using BSLT method had been carried out. Partition of the ethanol extract using n-hexane, chloroform and water was conducted and we found that the chloroform fractions was the most toxic with LC 50 of 43.65 ppm. The chloroform fractions were then separated by column chromatography using chloroform: ethyl acetate (7:3) as eluent and 5 fractions (F A -F E ) were obtained. Fraction A was the most toxic with LC 50 of 52.48 ppm. Identification the chemical compounds of the toxic isolates (F A ) was conducted by using GC-MS showing eight (8) compounds which are hexadecanoic acid methyl ester, 9-heneicosene, 9-ctadecenoic acid methyl ester, octadecanoic acid methyl ester, 1,2-benzenedicarboxylic acid bis-(2-ethylhexyl) ester, octacosane, n-heneicosane, and tetratetracontane.
Keywords: Callyspongia aerizusa sponge, ethanol extract, toxicity test